In vitro screening of rumen fluid samples from indigenous African ruminants provides for rumen fluid with superior capacities to digest tannin-rich fodders - Odenyo, A.A.; McSweeney, C.S.; Palmer, B.; Negassa, D.; Osuji, P.O. (1999)
The capabilities of rumen fluid sources from indigenous African ruminants and hindgut fluid from zebra to ferment leaves of Acacia angustissima, Calliandra calothyrsus, Leucaena diversifolia, Leucaena leucocephala, Leucaena pallida, and Tephrosia bracteolata were evaluated to determine the presence of tannin tolerant or degrading microbes. In vitro gas and ammonia production and loss of neutral detergent fibre were estimated as indices for fermentation. The effect of polyethylene glycol (PEG) on fermentation was tested. The ability of microorganisms in rumen fluid sources to grow in the presence of tannin extracts or tannic acid was also tested and their disappearance was determined by HPLC. There was a significant (P<0.001) rumen fluid source X fodder type interaction with all variables studied. The highest gas and ammonia production was from samples incubated with rumen fluid from dik-dik and goat. Addition of PEG enhanced fermentation with various rumen fluid sources and from some plant leaves but its effect was greatest (P<0.001) in A. angustissima. HPLC results showed that tannin and phenolic monomers were hydrolysed by all rumen fluid sources. The conclusion from this work was that rumen fluid from goat, gazelle, Gunther's dik-dik, and impala effectively fermented tannin-rich fodders and therefore may harbour tannin tolerant or degrading microorganisms.